Exposure to parental depression in childhood and memory trajectories in mid- and later life - Zhenmei Zhang; Seung-won Emily Choi; Yu Guo (PLoS ONE, 2026)
Little is known about whether childhood exposure to parental mental health problems, a significant stressor in early life, influences an individual’s memory trajectories in mid- and later life. Drawing on data from four waves (2011–2018) of the China Health and Retirement Longitudinal Study (CHARLS) and its supplement, the 2014 Life History Survey, we used the latent growth curve modeling technique to investigate whether exposure to parental depression in childhood is associated with memory trajectories of Chinese older adults. Our analytic sample included 7,097 respondents aged 50 and above who were raised by both parents. Results show that individuals who recalled having both parents depressed during their childhood had lower memory scores at baseline compared to their non-exposed counterparts, even after controlling for childhood socioeconomic status and health. These differences remained stable over the 7-year follow-up. Educational attainment and adult health—particularly depressive symptoms—explained the lower episodic memory scores observed in individuals who experienced both parents’ depression during childhood. Surprisingly, individuals who reported having only one parent (either mother or father) depressed during their childhood did not show significantly different memory trajectories compared to their non-exposed counterparts. The findings underscore the long arm of parental mental health on cognitive function in later life and highlight the importance of preventing and treating parental depression through a child’s formative years.